Business Strategy Formulation for PT Ardhia Multi Parama - Pratama, Teddy Apriliandi; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
The business situation of digital video-audio industry will be analyzed from the data that already collected from observation, interview, and library studies to determine the opportunity in this industry still exist or not. Some analyzing of the internal-external company is the second phase after analyze the business situation, it’s done to get some information about how strong the company to compete with other competitors. The analyzing are using Porter five force’s, SWOT analysis, and value chain analysis. So the business issue of the company is how to win the competition with the current condition. After analyzing all of the situation of the company, the writer determine what kind of strategy to use by formulating the strategy using SWOT Matrix and Business Model canvas. The recommendeation for the company is to use differentiation strategy because the result after analyzing the company have strong internal condition, but there are some threats from the external. So the business issue of the company is how to win the competition with the current condition. Strategy Implementation involves establishing programs to create a series of new organizational activities, budgets to allocate funds to the new activities, and procedures to handle the day-to-day details. With the commitment from all of the employees in implementing the proposed program, it can be expected can be sustain and grow to be one of the most famous production house in Indonesia. Keywords : Digital Video-Audio, Production House